2017
DOI: 10.1016/j.jpainsymman.2016.12.325
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Symptom Burden Among Cancer Patients With Different Stages of Cachexia

Abstract: This study identified higher symptom burden in cancer patients with cachexia and it increased with the stages of cachexia, which emphasized the importance of screening in multiple co-occurring symptoms for cachexia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 43 publications
2
33
0
2
Order By: Relevance
“…2 A randomized trial reported that a low skeletal muscle mass (sarcopenia) due to cachexia was associated with depression and quality of life in patients with advanced cancer. 16 Other studies on cancer patients revealed that systemic inflammation or elevated CRP levels were related to pain, anorexia, dyspnoea, fatigue, sleep disturbance, activities of daily living disabilities, and survival, [8][9][10][11][12][13][14][15] that these symptoms rarely existed in isolation, 11,13,39 and that pain, fatigue, and sleep disturbance were the basis of a symptom cluster in combination with reduced physical function. 14 A cross-sectional study showed a higher physical and psychological symptom burden (including pain, fatigue, sleep disturbance, distress, and anxiety) in patients with cancer cachexia, which increased with the stages of cachexia, and these findings emphasized the importance of screening for multiple co-occurring symptoms in cachexia patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 A randomized trial reported that a low skeletal muscle mass (sarcopenia) due to cachexia was associated with depression and quality of life in patients with advanced cancer. 16 Other studies on cancer patients revealed that systemic inflammation or elevated CRP levels were related to pain, anorexia, dyspnoea, fatigue, sleep disturbance, activities of daily living disabilities, and survival, [8][9][10][11][12][13][14][15] that these symptoms rarely existed in isolation, 11,13,39 and that pain, fatigue, and sleep disturbance were the basis of a symptom cluster in combination with reduced physical function. 14 A cross-sectional study showed a higher physical and psychological symptom burden (including pain, fatigue, sleep disturbance, distress, and anxiety) in patients with cancer cachexia, which increased with the stages of cachexia, and these findings emphasized the importance of screening for multiple co-occurring symptoms in cachexia patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 A cross-sectional study showed a higher physical and psychological symptom burden (including pain, fatigue, sleep disturbance, distress, and anxiety) in patients with cancer cachexia, which increased with the stages of cachexia, and these findings emphasized the importance of screening for multiple co-occurring symptoms in cachexia patients. 13 A meta-analysis revealed that interleukin-6 (IL-6), tumour necrosis factor, and CRP were elevated in non-cancer patients with depression. 40 Other studies demonstrated that depression and cognitive dysfunction were associated with systemic inflammation due to the breakdown of the serotonergic system in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo de revisão mostra que este perfil é comum nos pacientes com câncer (9) e também que esses pacientes costumam ter uma fé, cuja contribuição positiva na aceitação e no enfrentamento de doenças é reconhecida, talvez por seu papel na manutenção do ânimo, na vontade de viver e na satisfação com a vida (10) . Muitas vezes o tratamento antineoplásico torna-se a renovação da esperança para o paciente oncológico (11)(12)(13)(14)(15)(16)(17)(18)(19) .…”
Section: Discussionunclassified
“…The prevalence of sensory symptoms (numbness, tightness, tingling, and burning) reported in patients with advanced cancer and in palliative care patients varies widely from 6 to 36% ( 16 19 ). These variations may be caused by the different characteristics of the populations investigated, but also by the differing assessment methods used.…”
Section: Discussionmentioning
confidence: 99%